TMPRSS2-ERG gene fusion in prostate cancer - Burdova, Alena; Bouchal, Jan; Tavandzis, Spiros; Kolář, Zdeněk (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
BACKGROUND: The TMPRSS2-ERG gene fusion is one of the most widely spread chromosomal rearrangements in carcinomas. Since its discovery, a number of studies have examined its diagnostic, prognostic and therapeutic implications for prostate cancer where suitable biomarkers are still lacking. The publication data are inconsistent. The aim of this review was to critically evaluate the current clinical impact of this gene fusion. METHODS: The PubMed online database was used to search relevant reviews and original articles. RESULTS: Although the TMPRSS2-ERG gene fusion appears to be a suitable diagnostic biomarker, the prognostic implications of this gene fusion are still unclear. Several new strategies for therapeutically targeting ETS fusions and their modulators have been identified and are currently being investigated. CONCLUSION: Due to the heterogeneity of prostate cancer, the combination of several biomarkers is necessary to accurately assess the presence of prostate cancer, predict its potential clinical outcome and decide on appropriate therapy (e.g. PARP inhibitors).
Keywords: fúze genů; mužské pohlaví; nádory prostaty; prognóza; fúzní onkogenní proteiny; nádorové biomarkery; Oncogene Proteins, Fusion; Humans; Prostatic Neoplasms; Male; Prognosis; lidé; Gene Fusion; Biomarkers, Tumor